Pengembangan Inovasi Dan Pembuatan Laporan Keuangan Sederhana Pada UMKM Bolu Jadul Bu Tati - Bobby Himawan; Jesica Shindi Nur Fadillah; Ratna Sulastri; Febry Aulia Finandhita; Ahmad Yasin Thalib (STIKes Ibnu Sina Ajibarang, 2023)
This program is a form of community service in the economic sector, especially for MSME players, by helping them with mentoring and providing innovation and finding solutions to obstacles faced in their businesses. The target of the MSMEs who are being assisted is Mrs. Tati, who is an MSME who sells Old School Bolu. The problem is that these MSMEs don't have a distinctive characteristic and don't have an attractive logo, so this will result in not attracting the attention of consumers. Apart from that, the appearance of Mrs. Tati's Instagram account hasn't been updated for a long time because Mrs. Tati doesn't understand how to use Instagram as an advertising medium. So this activity provides a solution to this problem by providing education about the use of social media, namely adding content to cellphone numbers, addresses and also online orders as well as helping with practical financial recording using the Kasvlo application